Settings and functions related to simultaneous use of alcohol with marijuana or cocaine among clients in treatment for substance abuse - Pakula, B.; Macdonald, S.; Stockwell, Tim (Informa Healthcare, 2009)
Objectives: The paper identifies the central theoretical components for developing a typology of alcohol use with other substances. The settings and functions related to the simultaneous use of alcohol with marijuana or cocaine are examined using a dataset from a study of treatment clients in Ontario, Canada (data collected between the years 2003 and 2005). Methods: A cross-sectional design was used where patients 18 years or older completed a self-administered questionnaire upon admission to various treatment programs. Clients who reported using marijuana (n = 499) or cocaine (n = 375) in the past year were asked how often they use these substances in combination with alcohol. Findings: Simultaneous use is very common among treatment clients, with differences in the settings and functions associated with alcohol used in combination with cocaine or marijuana, and by various sociodemographic characteristics. The study's limitations are noted. Copyright © 2009 Informa Healthcare USA, Inc.